Recognition any Backward – Forward Effects of Transportation in Iran Economy - Eidouzehi, Emam Bakhsh Tireh (IJRDO - Journal of Business Management, 2018)
It is evident to everybody that transportation is one of the infrastructure and fundamental sections and a connective ring of different industries as well. This is because all activities are under the effects of this part and it is an important part of production-consumption cycle in each economy. Transportation is necessary to provide suitable facilities for industries and development of most economic plans. In this research we intend to study and calculate any preceding and latest coefficients of transportation and dispersion / sensitivity power indexes by integration of Input -Output table and 30-parts table. According to the results, it is obvious that transportation has high level of preceding and latest effects in state’s economy with the most preceding connections with industry and fuels and also highest rate of latest connection with industry and building sector.